1987
DOI: 10.1161/01.cir.76.6.1397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of procainamide and N-acetylprocainamide on atrial flutter: studies in vivo and in vitro.

Abstract: We studied the effects of procainamide and N-acetylprocainamide (NAPA) in a conscious dog preparation of atrial flutter resulting from circus movement around the tricuspid orifice. We also recorded transmembrane potentials of atrial tissues from the circus path in vitro. In 12 instrumented dogs, average flutter cycle length was 157 msec, the duration of the excitable gap was 73 msec, and conduction velocity was 0.75 m/sec. At 4 and 8 mg/kg, procainamide moderately prolonged cycle length, but did not terminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
2
12
1
Order By: Relevance
“…Early class III potassium channel blocking agents, including N-acetylprocainamide, clofilium, and d-sotalol, the latter predominantly a blocker of the rapidly activating component of delayed rectifier potassium current, I Kr (Sanguinetti and Jurkiewicz, 1990), terminated atrial arrhythmia in this model while producing greater increases in atrial refractoriness compared with slowing of conduction (Wu and Hoffman, 1987;Spinelli and Hoffman, 1989;Wu et al, 1989b). The modest slowing of flutter observed with class III agents has been attributed to increased refractoriness in the partially repolarized excitable gap, resulting in advancement of the reentrant wave front into less fully repolarized cells, thereby propagating at a reduced velocity (Wu et al, 1989b).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Early class III potassium channel blocking agents, including N-acetylprocainamide, clofilium, and d-sotalol, the latter predominantly a blocker of the rapidly activating component of delayed rectifier potassium current, I Kr (Sanguinetti and Jurkiewicz, 1990), terminated atrial arrhythmia in this model while producing greater increases in atrial refractoriness compared with slowing of conduction (Wu and Hoffman, 1987;Spinelli and Hoffman, 1989;Wu et al, 1989b). The modest slowing of flutter observed with class III agents has been attributed to increased refractoriness in the partially repolarized excitable gap, resulting in advancement of the reentrant wave front into less fully repolarized cells, thereby propagating at a reduced velocity (Wu et al, 1989b).…”
Section: Discussionmentioning
confidence: 91%
“…Class IA and IC sodium channel blocking agents tested previously in the canine Y-shaped atrial lesion model, including procainamide, quinidine, flecainide, and propafenone, terminated atrial flutter and produced a greater slowing of conduction and increases in flutter cycle length compared with changes in refractoriness (Wu and Hoffman, 1987;Spinelli and Hoffman, 1989;Wu et al, 1989a). It has been postulated that these agents terminate reentry by depressing conduction to a point where propagation fails (Spinelli and Hoffman, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental Study. In an animal model with a Y-shaped atrial lesion, Wu and Hoffman 39 have reported that procainamide could terminate sustained atrial flutter around the tricuspid ring. Termination was preceded by a marked increase in cycle length and correlated with depression of conduction rather than prolongation of refractoriness.…”
Section: Procainamidementioning
confidence: 99%
“…Recently, a conscious model for re-entry arrhythmia in the dog has 1 Author for correspondence. been developed (Frame et al, 1986;Wu & Hoffman, 1987). The arrhythmia is a result of re-entrant excitation propagated in a partially repolarized atrial tissue around the tricuspid ring (Frame et al, 1986;Wu et al, 1989a).…”
Section: Introductionmentioning
confidence: 99%
“…The circus movement is easy to induce, stable in cycle length, and persistent. Various antiarrhythmic agents have been studied in this model of arrhythmia (Wu & Hoffman, 1986;Frame & Colatsky, 1987;Spinelli & Hoffman, 1987;Wu & Hoffman, 1987).…”
Section: Introductionmentioning
confidence: 99%